2020
DOI: 10.3390/jcm9082420
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Platelet Counts in Major Trauma: The Impact of Haemostatic Resuscitation and Effects of Platelet Transfusion—A Sub-Study of the Randomized Controlled RETIC Trial

Abstract: Although platelets play a central role in haemostasis, the dynamics of platelet counts during haemostatic resuscitation, the response to platelet transfusion, and effects on clinical outcome are poorly described for trauma patients. As a sub-study of the already published randomized controlled RETIC Study “Reversal of Trauma-induced Coagulopathy using First-line Coagulation Factor Concentrates or Fresh-Frozen Plasma” trial, we here analysed whether the type of first-line haemostatic resuscitation influences th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…While a low platelet count has been consistently associated with both morbidity and mortality in trauma patients, the threshold and timing of platelet transfusion remains controversial [ 6 ]. Although the platelet count at admission was found to be a biomarker for trauma severity and predictive of outcome, including bleeding intensity and transfusion requirements [ 262 ], platelet counts are frequently within the normal range at hospital admission, but may decrease sharply in the following 1–2 h of haemostatic resuscitation and decline continuously thereafter, suggesting an important role for the treatment administered [ 310 ].…”
Section: Resultsmentioning
confidence: 99%
“…While a low platelet count has been consistently associated with both morbidity and mortality in trauma patients, the threshold and timing of platelet transfusion remains controversial [ 6 ]. Although the platelet count at admission was found to be a biomarker for trauma severity and predictive of outcome, including bleeding intensity and transfusion requirements [ 262 ], platelet counts are frequently within the normal range at hospital admission, but may decrease sharply in the following 1–2 h of haemostatic resuscitation and decline continuously thereafter, suggesting an important role for the treatment administered [ 310 ].…”
Section: Resultsmentioning
confidence: 99%
“…In an in vitro study questioning the optimal level of fibrinogen, Bollinger and co-workers found that only fibrinogen levels above 200 mg•dL −1 enhance total clot formation [26]. Previously published results from the RETIC study confirmed that early achievement of fibrinogen levels above 200 mg•dL −1 not only normalized FibA10, but also total clot firmness, reduced the rate of MT significantly, and reduced platelet count decline and the need for platelet transfusion [21,22].…”
Section: Discussionmentioning
confidence: 97%
“…However, fibrinogen is at least a contributing factor and also one, which can be influenced by therapy. Moreover, early achievement of fibrinogen levels above 200 mg•dL −1 exerts a platelet saving effect and platelets further augment stable clot formation and limitation of blood loss [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a substudy of the randomized, controlled RETIC trial has shown that platelet transfusion did not substantially improve platelet counts and that, after adjusting for injury severity, transfusion of platelets was associated with poor clinical outcomes. 30 However, the authors did conclude that there is no evidence of a causal relationship between platelet transfusion and poor outcomes and that platelet transfusion is more likely to be a surrogate marker of severe injury and massive bleeding, both of which are associated with mortality.…”
Section: Discussionmentioning
confidence: 99%